War of the microbial world: Acanthamoeba spp. interactions with microorganisms - Mungroo, Mohammad Ridwane (Folia Microbiol (Praha), 2021)
Acanthamoeba is known to interact with a plethora of microorganisms such as bacteria, fungi and viruses. In these interactions, the amoebae can be predatory in nature, transmission vehicle or an incubator. Amoebae consume microorganisms, especially bacteria, as food source to fulfil their nutritional needs by taking up bacteria through phagocytosis and lysing them in phagolysosomes and hence play an eminent role in the regulation of bacterial density in the nature and accountable for eradication of around 60% of the bacterial population in the environment. Acanthamoeba can also act as a “Trojan horse” for microbial transmission in the environment. Additionally, Acanthamoeba may serve as an incubator-like reservoir for microorganisms, including those that are pathogenic to humans, where the microorganisms use amoebae’s defences to resist harsh environment and evade host defences and drugs, whilst growing in numbers inside the amoebae. Furthermore, amoebae can also be used as a “genetic melting pot” where exchange of genes as well as adaptation of microorganisms, leading to higher pathogenicity, may arise. Here, we describe bacteria, fungi and viruses that are known to interact with Acanthamoeba spp.